Controlled hydrolysis of cheese whey proteins using trypsin and alpha-chymotrypsin - Galvao, CMA; Silva, AFS; Custodio, M. F.; Monti, Rubens [UNESP]; Giordano, RDC (Humana Press Inc, 2001)
This study examined the production of protein hydrolysates with controlled composition from cheese whey proteins. Cheese whey was characterized and several hydrolysis experiments were made using whey proteins and purified beta -lactoglobulin, as substrates, and trypsin and a-chymotrypsin, as catalysts, at two temperatures and several enzyme concentrations. Maximum degrees of hydrolysis obtained experimentally were compared to the theoretical values and peptide compositions were calculated. For trypsin, 100% of yield was achieved; for alpha -chymotrypsin, hydrolysis seemed to be dependent on the oligopeptide size. The results showed that the two proteases could hydrolyze beta -lactoglobulin. Trypsin and alpha -chymotrypsin were stable at 40 degreesC, but a sharp decrease in the protease activity was observed at 55 degreesC.
Keywords: cheese whey; beta-lactoglobulin; protein hydrolysates; trypsin; alpha-chymotrypsin